Dietary change in Bangladesh from 1985 to 2010 - Waid, Jillian; Gabrysch, Sabine (Global food security, 2018)
In many countries, dietary change is tracked using food supply data from the Food and Agriculture Organization's food balance sheets. It is difficult to draw conclusions on individual or sub-national food consumption from these data and impossible to study inequalities. We analyzed seven Household [Income and] Expenditure Surveys (H[I]ES) in Bangladesh from 1985 to 2010 to track changes in consumption patterns. There was a broad national trend of incorporating more non-starch foods into the diet, similar to what is seen in food supply data, but dietary diversification was limited among the poorest quintile. There were also several differences to estimates from food supply data, e.g. vegetable consumption was much higher. Further analyses of this kind will help to better understand dietary change.
Gesehen am 23.04.2019